MENGUKUR ENGAGEMENT WARGA NEGARA DALAM INTERAKSI MEDIA SOSIAL (STUDI PADA 32 AKUN RESMI FACEBOOK PEMERINTAH KABUPATEN/KOTA DI JAWA TENGAH) - Anton Purwadi; Arif Budy Pratama; Raden Mas Mahendradi (Yogyakarta State University, 2019)
The purpose of this research is to measure citizen engagement on social media interaction of 32 regencies/ municipals government official Facebook accounts in Central Java Province.To do so, a quantitative approach was conducted. The data ware collected from 32 official accounts and categorized into five aspects namely like, comment, share, followers, and post. The result of engagement measuement based on likes, comments, share, followers, and posts, shows various level of engagement among municiplities or regencies. The average engagement in facebook interaction is 0.0432. Purworejo regency official facebok account placed in the first rank with 0.2981. Followed by Grobogan Regency official facebok account as second winner by 0.2524. Given this result, local government units, specifically, those deal with strategic public communication may draw lesson learns to manage their official facebook account. A good management of social media is needed to improve citizen engagement.